Comparing In-Person to Videoconference-Based Cognitive Behavioral Therapy for Mood and Anxiety Disorders: Randomized Controlled Trial - Stubbings, Daniel; Rees, Clare; Roberts, Lynne; Kane, Robert (Journal of Medical Internet Research, 2013)
Background: Cognitive-behavioral therapy (CBT) has demonstrated efficacy and effectiveness for treating mood and anxiety disorders. Dissemination of CBT via videoconference may help improve access to treatment. Objective: The present study aimed to compare the effectiveness of CBT administered via videoconference to in-person therapy for a mixed diagnostic cohort. Methods: A total of 26 primarily Caucasian clients (mean age 30 years, SD 11) who had a primary Diagnostic and Statistical Manual of Mental Disorders, 4th edition text revision (DSM-IV-TR) diagnosis of a mood or anxiety disorder were randomly assigned to receive 12 sessions of CBT either in-person or via videoconference. Treatment involved individualized CBT formulations specific to the presenting diagnosis; all sessions were provided by the same therapist. Participants were recruited through a university clinic. Symptoms of depression, anxiety, stress, and quality of life were assessed using questionnaires before, after, and 6 weeks following treatment. Secondary outcomes at posttreatment included working alliance and client satisfaction.Results: Retention was similar across treatment conditions; there was one more client in the videoconferencing condition at posttreatment and at follow-up. Statistical analysis using multilevel mixed effects linear regression indicated a significant reduction in client symptoms across time for symptoms of depression (P<.001, d=1.41), anxiety (P<.001, d=1.14), stress (P<.001, d=1.81),and quality of life (P<.001, d=1.17). There were no significant differences between treatment conditions regarding symptoms of depression (P=.165, d=0.37), anxiety (P=.41, d=0.22), stress (P=.15, d=0.38), or quality of life (P=.62, d=0.13). There were no significant differences in client rating of the working alliance (P=.53, one-tailed, d=–0.26), therapist ratings of the working alliance (P=.60, one-tailed, d=0.23), or client ratings of satisfaction (P=.77, one-tailed, d=–0.12). Fisher’s Exact P was not significant regarding differences in reliable change from pre- to posttreatment or from pretreatment to follow-up for symptoms of depression (P=.41, P=.26), anxiety (P=.60, P=.99), or quality of life (P=.65, P=.99) but was significant for symptoms of stress in favor of the videoconferencing condition (P=.03, P=.035). Difference between conditions regarding clinically significant change was also not observed from pre- to posttreatment or from pretreatment to follow-up for symptoms of depression (P=.67, P=.30), anxiety (P=.99, P=.99), stress (P=.19, P=.13), or quality of life (P=.99, P=.62). Conclusions: The findings of this controlled trial indicate that CBT was effective in significantly reducing symptoms of depression, anxiety, and stress and increasing quality of life in both in-person and videoconferencing conditions, with no significant differences being observed between the two.